Macroeconomic fluctuations and mortality rates - Lim, Christian Bernard Y. (School of Economics, University of the Philippines Diliman, 2018)
The relationship between macroeconomic fluctuations, and health, represented by mortality rates, is one that has produced different results across different studies. Ruhm_s studies in the United States finds a procyclical relationship between the two variables_ mortality rates decline during economic downturns as people are able to live out healthier lifestyles. However, a study by Svensson and Kruger, using Swedish data from 1800 to 2000, finds both procyclical and countercyclical relationships between macroeconomic variables and mortality rates, as the leading cause of death varies from violence to cancer. This paper aims to observe the relationship between these variables in the 10 ASEAN countries. The findings suggest that there is no significant relationship between the macroeconomic variables and mortality rates of the young and old age groups. However, there is a significant relationship between the macroeconomic variables and mortality rates of the working population. As GDP per capita increases, mortality rates of the working population decreases, which could be explained by the fact that they are the age group that is the most affected by changes in the business cycle.